MODERN DIRECT DEMOCRACY: THE POTENTIAL OF E-GOVERNMENT IN UKRAINIAN REALITY - Кудрявцев, О.Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The article deals with the problems of implementing the model of e-governance based on the latest information and communication technologies in the Ukrainian political realities. Were characterized the existing achievements, highlighted the potential prospects and development trends.